Nocturnal dissolved organic matter release by turf algae and its role in the microbialization of reefs. (4th July 2022) - Mueller, Benjamin; Brocke, Hannah J.; Rohwer, Forest L.; Dittmar, Thorsten; Huisman, Jef; Vermeij, Mark J. A.; de Goeij, Jasper M.
Abstract: The increased release of dissolved organic matter (DOM) by algae has been associated with the fast but inefficient growth of opportunistic microbial pathogens and the ongoing degradation of coral reefs. Turf algae (consortia of microalgae and macroalgae commonly including cyanobacteria) dominate benthic communities on many reefs worldwide. Opposite to other reef algae that predominantly release DOM during the day, turf algae containing cyanobacteria may additionally release large amounts of DOM at night. However, this night‐DOM release and its potential contribution to the microbialization of reefs remains to be investigated. We first tested the occurrence of hypoxic conditions at the turf algae–water interface, as a lack of oxygen will facilitate the production and release of fermentation intermediates as night‐time DOM. Second, the dissolved organic carbon (DOC) release by turf algae was quantified during day time and nighttime, and the quality of day and night exudates as food for bacterioplankton was tested. Finally, DOC release rates of turf algae were combined with estimates of DOC release based on benthic community composition in 1973 and 2013 to explore how changes in benthic community composition affected the contribution of night‐DOC to the reef‐wide DOC production. A rapid shift from supersaturated to hypoxic conditions at the turf algae–water interface occurred immediately after the onset of darkness, resulting in night‐DOC release rates similar to those during daytime. Bioassays revealed major differences in the quality between day and night exudates: Night‐DOC was utilized by bacterioplankton two times faster than day‐DOC, but yielded a four times lower growth efficiency. Changes in benthic community composition were estimated to have resulted in a doubling of DOC release since 1973, due to an increasing abundance of benthic cyanobacterial mats (BCMs), with night‐DOC release by BCMs and turf algae accounting for >50% of the total release over a diurnal cycle. Night‐DOC released by BCMs and turf algae is likely an important driver in the microbialization of reefs by stimulating microbial respiration at the expense of energy and nutrient transfer to higher trophic levels via the microbial loop, thereby threatening the productivity and biodiversity of these unique ecosystems. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Resumen: El incremento de la liberación de materia orgánica disuelta (MOD) por parte de las algas se ha asociado con el crecimiento rápido pero ineficaz de microorganismos patógenos oportunistas y la continua degradación de los arrecifes coralinos. Los céspedes algales (consorcios de micro y macroalgas que suelen incluir cianobacterias) dominan las comunidades bentónicas de muchos arrecifes de todo el mundo. A diferencia de otras algas de arrecife que liberan predominantemente MOD durante el día, los céspedes algales que contienen cianobacterias pueden liberar adicionalmente grandes cantidades de MOD durante la noche. Sin embargo, esta liberación nocturna de MOD y su potencial contribución a la microbialización de los arrecifes aún falta por ser investigada. En primer lugar, investigamos la existencia de condiciones de hipoxia en la interfase entre los céspedes algales y el agua, ya que la falta de oxígeno facilitaría la producción y liberación de productos intermedios de fermentación como MOD nocturna. En segundo lugar, cuantificamos la liberación de carbono orgánico disuelto (COD) por los céspedes algales durante el día y la noche, y se comprobó la calidad de los exudados diurnos y nocturnos como alimento para el bacterioplancton. Finalmente, las tasas de liberación de MOD de los céspedes algales se combinaron con las estimaciones de liberación de COD basadas en la composición de la comunidad bentónica en 1973 y 2013 para explorar cómo los cambios en la composición de la comunidad bentónica afectaron a la contribución de MOD nocturna y a su vez a la producción de COD en todo el arrecife. En ausencia de luz, se produjo inmediatamente un cambio rápido de condiciones sobresaturadas a condiciones hipóxicas en la interfaz entre los céspedes algales y el agua, lo que dio lugar a tasas de liberación de COD nocturnas similares a las diurnas. Los bioensayos revelaron importantes diferencias en la calidad de los exudados diurnos y nocturnos: el bacterioplancton utilizó el COD nocturno dos veces más rápido que el COD diurno, pero su eficiencia de crecimiento fue cuatro veces menor. Se estimó que los cambios en la composición de la comunidad bentónica han dado lugar a una duplicación de la liberación de MOD desde 1973 debido a la creciente abundancia de tapetes de cianobacterias bentónicas, y que la liberación nocturna de COD por parte de estos tapetes y los céspedes algales representa >50% de la liberación total durante un ciclo diurno. El COD nocturno que es liberado por los tapetes de cianobacterias bentónicas y los céspedes algales es probablemente un importante promotor de la microbialización de los arrecifes al estimular la respiración microbiana a expensas de la transferencia de energía y nutrientes a los niveles tróficos superiores a través del bucle microbiano y, por tanto, amenaza la productividad y la biodiversidad de estos ecosistemas únicos.